DETERMINATION OF ELECTROMAGNETIC PARAMETERS OF A LINEAR STEPPER DEVICE - СМОЛЯНІНОВ, В. Г.; СУХОПАРА, О. М. (Technologies and Engineering, 2024)
Purpose. Consideration of the design and determination of the electromagnetic parameters of a linear stepper device during step-by-step movement of the moving link, obtainingformulas in analytical form for their calculation and improving the operating efficiency of the linear stepper device. Methodology. When conducting research on a linear stepper device with the step-by-step movement of a moving link, the theory of electrical and magnetic circuits was used, and calculation of electromagnetic parameters was carried out taking into account the design parameters of the switched-on stator section of a linear stepper device that changes when the moving link moves by the step size. Findings. The design features of n -winding linear stepper devices are considered and the operation of the three-section structure of a linear stepper device is analyzed. An analysis of changes in the electromagnetic parameters of the magnetic circuit in the section of the switched-on stator winding of a linear stepper device has been carried out, and the dependence of the magnetic resistance in individual sections of the magnetic circuit on the design parameters has been found, and the position of the moving link of the linear stepper device. The correspondence between the change in inductive parameters when moving the moving link and the change in electrical characteristics in the section of the switched-on stator winding of a linear stepper device has been established. Originality. The intervals of change in magnetic resistance when moving the moving link of a linear stepper device by a step value are determined and analytical expressions for their calculation are obtained. The change in inductive parameters when moving the moving link of a linear stepper device by a step size has been studied, and analytical expressions have been found for calculating the inductance and its derivative for the convenience of calculations, presented in dimensionless form. Practical value. The results obtained can be used in the development of new designs of linear stepper devices, and monitoring changes in electromagnetic parameters and electrical characteristics in the switched-on winding section of linear stepper devices increases the efficiency of their operation.